Convergence of Customary, Islamic and State Law in Sasak Community Marriages - Joko Susilo; Wulan Safitri (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research examines the interaction between customary law, Islamic law and state law in the context of marriage in the Sasak community, Lombok, Indonesia. Through a descriptive qualitative approach, this research collects data using in-depth interviews, participant observation, and documentation studies to understand the complex dynamics of interlegality. The research results show that the Sasak people actively navigate the tensions and synergies between the three legal systems in their marriage practices. Legal conflicts often arise from differences in the interpretation and application of customary, Islamic and state law, especially in aspects of dowry, inheritance and child custody. The Sasak people use mechanisms such as mediation by traditional and religious leaders and adaptation of customary legal practices to resolve this conflict. This research provides important insights into how multicultural societies such as the Sasak manage their legal diversity, which can help in the development of legal policies that are more inclusive and sensitive to cultural diversity in Indonesia.